Plasmid-mediated antibiotic resistance inPseudomonas (Burkholderia) cepacia frombrackish water aquaculture farms - Kumar, Rakesh; Surendran, P K (Indian Journal of Fisheries, 2014)
The study determined the resistance pattern of Pseudomonas (Burkholderia)cepacia isolated from brackish water aquaculture farms. Forty five Pseudomonascepacia isolates were assayed for antibiotic susceptibility test with a set of nineantibiotics viz. kanamycin, nitrofurantoin, chloramphenicol, sulphamethizol,gentamicin, oxytetracycline, rifampicin, neomycin and streptomycin. All 45isolates were resistant to sulphamethizol, oxytetracycline, rifampicin,chloramphenicol and streptomycin (100%) and all were sensitive to gentamicinand neomycin (100%), whereas, 13% isolates were resistant to kanamycin. Strainsshowing similar resistance pattern against seven of nine antibiotics tested wereassayed for the presence of plasmid. All six strains harboured three, high copynumber small plasmid of size 4kb, 2kb and < 2.0 kb. Plasmid based antibioticresistance were determined with curing and transformation. P. cepacia plasmidswere cured with Sodium dodecyl sulfate (SDS), Acridine Orange (AO) andEthidium Bromide (EtBr) at elevated temperature. Acridine Orange (AO) andEthidium Bromide (EtBr) were better curing agents for P.cepacia. The lostproperty due to curing was regained by the transformants, as they were turnedresistant against kanamycin and streptomycin. There was a marked differencein the cured and wild strains in the colony morphology and antibiotic patterndue to plasmids.